Control interno y su relación con gestión administrativa en el Hospital Regional de Loreto año 2023 - Villacorta Lima, Socorro (Universidad Nacional de la Amazonía Peruana, 2024)
The effective interrelation between internal control and another fundamental aspect such as administrative management in health establishments is essential for the success of government management in the field of health, both guarantee efficiency in the use of resources, improve quality of health services, comply with standards and regulations, prevent fraud and embezzlement, plan strategically, promote transparency and accountability, and adapt quickly to changes in the health environment, which is why the present The study aims to determine the relationship between internal control and administrative management at the Loreto Regional Hospital in 2023, with a quantitative approach, correlational level and non-experimental design, with a study population of 81 collaborators, the results show that it is not evident a significant relationship between the study variables, concluding that at the Loreto Regional Hospital, according to the perspective of the collaborators, a significant statistical relationship has not been identified between internal control and administrative management, administrative planning, administrative organization, administrative direction and administrative evaluation, with statistical significance values that vary between 0.154 and 0.761. However, despite the lack of statistical correlation, internal control shows notable strengths, especially in crucial areas such as institutional analysis, objective orientation and planning, opportunities are highlighted to strengthen internal control actions and improve administrative evaluation instruments. , administrative management, although it reveals strengths in the organizational structure and monitoring processes, points out specific areas that need attention and improvement to align more effectively with institutional objectives, evidencing the importance of continually evaluating and strengthening both internal control and management. administrative to optimize institutional performance.

La interrelación efectiva entre el control interno y otro aspecto fundamental como es la gestión administrativa en los establecimientos de salud es esencial para el éxito de la gestión gubernamental en el ámbito de la salud, ambos garantizan la eficiencia en la utilización de los recursos, mejorar la calidad de los servicios de salud, cumplir con normativas y regulaciones, prevenir fraudes y malversaciones, planificar estratégicamente, promover la transparencia y la rendición de cuentas, y adaptarse de manera ágil a cambios en el entorno de la salud, es por ello que el presentes estudio planteo determinar la relación entre el control interno y la gestión administrativa en el Hospital Regional de Loreto año 2023, con un enfoque cuantitativo, nivel correlacional y diseño no experimental, con una población de estudio de 81 colaboradores, los resultados muestras que no se evidencia una relación significativa entre las variables de estudio concluyendo que en el Hospital Regional de Loreto, según la perspectiva de los colaboradores, no se ha identificado una relación estadística significativa entre el control interno y la gestión administrativa, la planificación administrativa, la organización administrativa, la dirección administrativa y la evaluación administrativa, con valores de significancia estadística que varían entre 0.154 y 0.761. Sin embargo, a pesar de la falta de correlación estadística, el control interno muestra fortalezas notables, especialmente en áreas cruciales como análisis institucional, orientación de objetivos y planificación, se destacan oportunidades para fortalecer las acciones de control interno y mejorar los instrumentos de evaluación administrativa, la gestión administrativa, aunque revela fortalezas en la estructura organizativa y los procesos de monitoreo, señala áreas específicas que necesitan atención y mejora para alinearse más eficazmente con los objetivos institucionales, evidenciándose la importancia de evaluar y fortalecer continuamente tanto el control interno como la gestión administrativa para optimizar el desempeño institucional.
Keywords: Supervisión interna; Gestión; Organización y administración; Hospitales públicos; https://purl.org/pe-repo/ocde/ford#5.06.02